The Vasodilatory Response to CGRP of the Anterior and Posterior Cerebral Circulation in Migraine - Visočnik, Darja; Zaletel, Marjan; Žvan, Bojana; Zupan, Matija (Frontiers in Neurology, 2022)
Introduction Migraine aura can be associated with headache or it may occur without one, which suggests an independent mechanism for the aura and for migraine headache. The role of CGRP in migraine headache is well established, but the connection between CGRP and the aura is still lacking an explanation. Exogenous CGRP can induce CGRP headaches and migraine auras in patients with migraine. The results of our recent study suggest differences in the vascular response to CGRP stimulation between migraine without aura and migraine with aura. Therefore, we hypothesized that the magnitude of the posterior cerebral circulation response in migraine with aura is greater than in migraine without aura and that CGRP stimulation has different effects on the anterior and posterior circulation in migraine with aura and migraine without aura. Methods By using transcranial doppler, we studied the hemodynamic effects of CGRP intravenous infusion at a rate of 1.5 mcg/min in 20 min on the mean arterial velocity in the middle cerebral artery and in the posterior cerebral artery in twenty patients with migraine and in a control group of twenty healthy subjects. The same CGRP effects on cerebral hemodynamics were analyzed separately for the group of patients with migraine with aura and the group of patients with migraine without aura. Fifteen patients with migraine (75%) had migraine without aura and 5 patients (25%) had migraine with aura. Results We found that migraine has a significant impact on the vasodilatory response of the anterior (B = 4,249, SE = 1.023, r = 0.363, p < 0.001) and posterior cerebral circulation (B = 3.634, SE = 1.461, r = 0.227, p = 0.014). Migraine with aura was significantly associated with changes in the anterior (B = 2.558, SE = 0.880, r = 0.275, p = 0.005) and posterior cerebral circulation (B = 7.565, SE = 2,368, r = 0.359, p = 0.002), while migraine without aura was only significantly associated with changes in the anterior circulation. In addition, we established a significant impact of migraine with aura on VR PCA (B = 5.901, SE = 2,546, r = 0.291, p = 0.024). Conclusion We conclude that TVR in the posterior cerebral circulation might be enhanced in MA and that aura might be a consequence of TVR enhancement.